Greenwashing in Indonesia: Deceptive Claims and Corporate Social Responsibility (CSR) - Yonandi, Caecilia Patrice; Lie, Gunardi (Peneliti.net, 2025)
The paper investigates the phenomenon greenwashing in Indonesia, examining its prevalence among corporations and assessing the effectiveness of legal frameworks designed to curb it. Greenwashing is characterized as deceptive claims about a company’s environmental practices, and common practices include misleading eco-labels on products, exaggerated sustainability claims, or irrelevant and misfocused green initiatives. Through a comprehensive methodology of legal analysis, corporate social responsibility (CSR) evaluations, and media investigations, the research identifies systemic flaws in Indonesia’s legal system that allow greenwashing to thrive. These include ambiguous legal definitions, insufficient regulations against false environmental claims, and weak enforcement. Together, they not only mislead the public into mindless consumption, but also undermine genuine environmental advocacy and governmental regulatory efforts. To address these challenges, the paper recommends strengthening legal regulations and enforcement within all sectors to prevent deceptive claims, boosting corporate transparency and accountability, and enhancing consumer education to promote a more critical approach to environmental claims. Additionally, the paper suggests further research on industry-specific greenwashing and cross-border comparisons to find more robust countermeasure practices by other governments. Addressing greenwashing is crucial for Indonesia’s environmental sustainability, with the need for a concerted effort from all stakeholders, including legal, corporate, and public sectors to establish a truly sustainable business environment.